Epigenetic pathogenesis of human papillomavirus in upper aerodigestive tract cancers. Issue 11 (11th September 2014) - Talukdar, Fazlur Rahman; Ghosh, Sankar Kumar; Laskar, Ruhina Shirin; Kannan, Ravi; Choudhury, Biswadeep; Bhowmik, Arup
<x xml:space="preserve">Abstract</x> Human papillomavirus (HPV) has been recently associated with squamous cell carcinoma of upper aerodigestive tract (SCC of UADT), but its possible role in promoting aberrant methylation in these tumors has largely remained unexplored. Herein, we investigated the association of HPV with aberrant methylation in tumor‐related genes/loci consisting of the classical CpG Island Methylator Phenotype (CIMP) panel markers (p16, MLH1, MINT1, MINT2, and MINT31) and other frequently methylated cancer‐related genes (DAPK1, GSTP1, BRCA1, ECAD, and RASSF1) and survival of UDAT cancers. The study includes 219 SCC of UADT patients from different hospitals of Northeast India. Detection of HPV and aberrant promoter methylation was performed by PCR and Methylation Specific PCR respectively. Association study was conducted by Logistic regression analysis and overall survival analysis was done by Kaplan–Meier plot. HPV was detected in 37% of cases, with HPV‐18 as the major high‐risk sub‐type. Although HPV presence did not seem to affect survival in overall UADT cancers, but was associated with a favourable prognosis in head and neck squamous cell carcinoma. Hierarchical clustering revealed three distinct clusters with different methylation profile and HPV presence. Among these, the CIMP‐high subgroup exhibited the highest HPV positive cases (66%). Furthermore, multivariate analysis revealed a strong synergistic association of HPV and tobacco towards modulating promoter hypermethylation in UADT cancer (OR = 27.50 [95% CI = 11.51–88.03] for CIMP‐high vs. CIMP‐low). The present study proposes a potential role of HPV in impelling aberrant methylation in specific tumor related loci, which might contribute in the initiation and progression of SCC of UADT. © 2014 Wiley Periodicals, Inc.